Position Paper on Applications Of Smart Contracts and Blockchain Technology - Wells, Penny; Probert, Georgia; Marke, Daniel; Konopka, Claudia (Blockchain Frontier Technology, 2023)
Blockchain technology makes it possible to handle a transaction decentralized. We intend to outline the history of blockchain technology in this position paper, go over one of its key components, the smart contract, and discuss some of its recent uses in the cryptocurrency, financial services, risk management, and Internet of Things industries.